2019
DOI: 10.1186/s12894-019-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches for treatment of ureteropelvic junction obstruction – a systematic review and network meta-analysis

Abstract: BackgroundMultiple surgical treatment options are available for the treatment of ureteropelvic junction obstruction (UPJO). The aim of this study is to compare the most frequently used technics in a comprehensive network approach.MethodsA systematic literature search of the EMBASE, MEDLINE and COCHRANE libraries was conducted in January 2018. Publications were included that evaluated at least two of the following surgical techniques: open pyeloplasty (OP), endopyelotomy (EP), laparoscopic (LP) and robot assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…Direct comparisons between LP and RAP have mostly been observational in nature[ 50 ] and randomized trials comparing the two techniques are few. [ 51 ] Until recently, systemic reviews and meta-analysis comparing LP with RAP reported conflicting results. [ 52 ] However, Uhlig et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct comparisons between LP and RAP have mostly been observational in nature[ 50 ] and randomized trials comparing the two techniques are few. [ 51 ] Until recently, systemic reviews and meta-analysis comparing LP with RAP reported conflicting results. [ 52 ] However, Uhlig et al .…”
Section: Resultsmentioning
confidence: 99%
“…recently performed a network meta-analysis of mostly adult patients with UPJO comparing the outcomes of open pyeloplasty, LP, RAP and endopyelotomy. [ 51 ] The authors report that RAP is associated with a significantly higher operative success rate compared to the LP, while the risk of peri-operative complications, urine leak, re-operation rate, blood transfusion rate and LOS were comparable. On including only the studies reporting 1-year follow up (13 of 24 studies), no difference in success rates was found between LP and RAP.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent systematic review of 26 retrospective and prospective studies showed no statistically significant differences between RALP and LP with respect to operative time (OR = −12.12; 95% CI −41.08–16.84; p = 0.412), and length of stay (OR = −0.87; 95% CI −3.23–1.49; p = 0.471). 30 …”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…RALP and LP yielded analogue results regarding overall mid and long-term complications (OR = 1; 95% CI 1–1; p = NA), urinary leakage (OR = 0.57; 95% CI 0.24–1.36; p = 0.206), transfusion rate (OR = 0.44; 95% CI 0.02–10.32; p = 0.613) and re-operation rate (OR = 0.32; 95% CI 0.01–8.24; p = 0.494). 41 …”
Section: Complicationsmentioning
confidence: 99%
“…Several methods can be used to treat UPJO, including open pyeloplasty (OP), endoscopic pyelotomy (EP), laparoscopy (LP) and robot assisted pyeloplasty (RP). The success rate of RP is the highest, the complication of LP is lower than that of OP, the success rate of EP is relatively low, but the operation time is the shortest of all surgical methods [ 6 ]. In clinical work, the management of crossing vessels has always been a difficult challenge in laparoscopic pyeloplasty (LP).…”
Section: Introductionmentioning
confidence: 99%